Are racial/ethnic minorities recently diagnosed with diabetes less likely than white individuals to receive guideline-directed diabetes preventive care? - Felippe O. Marcondes; David Cheng; Margarita Alegria; Jennifer S. Haas (BMC, 2021)
Abstract Background Diabetes mellitus has reached epidemic proportions in the United States. As the prevalence of diabetes continues to rise, the burden of disease is divided unevenly among different populations. Racial/ethnic disparities in diabetes care are pervasive, including the provision of care for prevention of complications. Prevention efforts should be focused on the time that immediately follows a diagnosis of diabetes. The aim of this study was to assess racial/ethnic differences in the receipt of guideline-directed diabetes care for complication prevention by individuals recently diagnosed with diabetes. Methods We used repeated cross-sections of individuals recently diagnosed with diabetes (within the past 5 years) from the National Health Interview Survey from 2011 to 2017. Multivariate regression was used to estimate the associations between race/ethnicity (non-Hispanic White, non-Hispanic Black and Hispanic) and guideline-directed process measures for prevention of diabetes complications (visits to an eye and foot specialist, and blood pressure and cholesterol checks by a health professional - each in the prior year). We assessed effect modification of these associations by socioeconomic status (SES). Results In a sample of 7,341 participants, Hispanics had lower rates of having any insurance coverage (75.9 %) than Non-Hispanic Whites (93.2 %) and Blacks (88.1 %; p<0.001). After adjustment for demographics, total comorbidities, SES, and health insurance status, Hispanics were less likely to have an eye exam in the prior year (OR 0.80; (95 % CI 0.65-0.99); p=0.04) and a blood pressure check (OR 0.42; (95 % CI 0.28-0.65); p<0.001) compared to Non-Hispanic Whites. There was no significant effect modification of race/ethnicity by SES. Conclusions Hispanics recently diagnosed with diabetes were less likely to receive some indicators of guideline-directed care for the prevention of complications. Lack of insurance and SES may partially explain those differences. Future work should consider policy change and providers' behaviors linked to racial/ethnic disparities in diabetes care.